A group-based, acceptance & commitment therapy intervention for chronic pain. Issue 4 (1st October 2020) - Cosio, David
ABSTRACT: As the effects of the opioid epidemic continue, the availability of interventions that address the emotional and psychological needs of people who suffer from chronic pain are increasingly necessary. Acceptance and commitment therapy (ACT) is one of the more actively researched psychological approaches amongst the third wave of developing psychotherapies. In fact, ACT has been shown to improve chronic pain in several different populations. In order to widen access to treatment, the use of group-based, ACT interventions with individuals who suffer from chronic, non-cancer pain should be made available in more traditional, mental health settings. The purpose of the current article is to describe a group-based, ACT intervention for people who suffer from chronic, non-cancer pain. A 10-session group intervention is outlined, and recommendations intended to increase the intervention's efficacy are provided.